Qur’anic Literacy Development in Madrasah Ibtidaiyah: A Case Study of BTQ Instruction - Umi Chafidhotul Khoiroh; Ali Mahsun (Journal Of Islamic Education And Pesantren, 2025)
Qur’anic literacy constitutes a foundational element in shaping students’ religiosity, moral conduct (adab), and character development in Islamic basic education. One of the strategies to strengthen Qur’anic literacy in madrasah ibtidaiyah is through Baca Tulis Al-Qur’an (BTQ) instruction. This study aims to examine BTQ learning as a practice of Qur’anic literacy in Islamic primary education by analyzing the instructional process, students’ literacy outcomes, as well as supporting and inhibiting factors in its implementation. Employing a qualitative approach with a case study design, the research was conducted at MI Sulaimaniyah Kauman Mojoagung. The research participants included the head of the madrasah, BTQ teachers, classroom teachers, and students. Data were collected through observation, in-depth interviews, and documentation, and were analyzed interactively through data reduction, data display, and conclusion drawing using triangulation techniques. The findings indicate that structured BTQ instruction—implemented through systematic teaching methods, ability-based student grouping, routine Qur’an reading practices, and tiered evaluation—contributes positively to the enhancement of students’ Qur’anic literacy. Qur’anic literacy is reflected not only in improved reading and writing skills but also in the development of adab, learning discipline, and students’ religious attitudes. However, the effectiveness of BTQ instruction is influenced by differences in students’ initial abilities and the lack of consistent Qur’an reading practices within the family environment. Therefore, strengthening Qur’anic literacy requires sustained synergy between the madrasah and families to ensure long-term impact in Islamic basic education.